2018
DOI: 10.1111/hiv.12634
|View full text |Cite
|
Sign up to set email alerts
|

Using behavioural insights to increase HIV self‐sampling kit returns: a randomized controlled text message trial to improve England's HIV self‐sampling service

Abstract: ObjectivesThe aim of the study was to determine whether behaviourally informed short message service (SMS) primer and reminder messages could increase the return rate of HIV self‐sampling kits ordered online.MethodsThe study was a 2 × 2 factorial design randomized control trial. A total of 9585 individuals who ordered a self‐sampling kit from http://www.freetesting.hiv different SMS combinations: 1) standard reminders sent days 3 and 7 after dispatch (control); 2) primer sent 1 day after dispatch plus standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…The acceptance process is crucial in defining the profile of participants, as it was strongly associated with individual sociodemographic characteristics. As previously found, a young age and high school diploma were associated with a better overall participation rate [7,12]. Men aged under 30 years had a better acceptance rate in our study, which impacts their overall participation, even if they returned the kit at the same rate as older participants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The acceptance process is crucial in defining the profile of participants, as it was strongly associated with individual sociodemographic characteristics. As previously found, a young age and high school diploma were associated with a better overall participation rate [7,12]. Men aged under 30 years had a better acceptance rate in our study, which impacts their overall participation, even if they returned the kit at the same rate as older participants.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have analyzed the factors associated with HIV SSKs use, showing that users have a higher education level, better income, and are younger [7,9] than those who do not use it. Compared to heterosexual men, MSM also tend to be more willing to use such services [7,[9][10][11][12][13][14][15]. Most SSKs propose blood sampling for HIV screening or local sampling for Ct/Ng screening.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective combination was the behaviourally informed primers and reminders compared to standard remindersa 4 percentage point increase was observed. But, like the present study, despite a primer (or pre-notification) being included in the most effective combination, further analysis demonstrated that only the behaviourally informed reminders were independently effective and not the primers [38].…”
Section: Discussionsupporting
confidence: 50%
“…Reminders also suggest proactive behaviour to book an appointment whereas there are no direct actions associated with pre-notifications. The authors of another recent factorial study explored combinations of behaviourally informed pre-notification and reminder texts to increase return of self-sampling HIV kits [38]. The most effective combination was the behaviourally informed primers and reminders compared to standard remindersa 4 percentage point increase was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the reminder prompts should be sent and what the reminder prompts should say is debated. Other studies suggest that reminder prompts that prime positive social norms 36 or that increase people's knowledge of supportive information 37 may encourage health behaviour better than text messages without such behaviourally informed content. What the reminder prompt should say in each study could be decided after considering the specific barriers of and facilitators to the desired behaviour using a diagnostic tool, like the COM‐B model 38 …”
Section: Discussionmentioning
confidence: 99%